Energy compensation in a meal preceded by low-calorie sweetener- and sugar-containing preload - Wan Mahmood, Wan Fathin Fariza; Mamat, Nik Mazlan; Mohd Abu Bakar, Wan Azdie; Mohd Shukri, Nor Azwani (2015)
Low-calorie sweetener (LCS) has been an alternative for sugar in calorie-controlled diet but its benefit is debatable in weight reduction effort when consumers attempt to reinstate the reduced calories during the following meals.